The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/su13137377
|View full text |Cite
|
Sign up to set email alerts
|

Deliberative Forms of Democracy and Intergenerational Sustainability Dilemma

Abstract: Intergenerational sustainability (IS) has emerged as the most serious social problem reflecting climate change and accumulation of public debt in modern democratic societies, undermining the potential interests and concerns of future generations. However, little is known about whether or not deliberative forms of democracy with majority voting help support at maintaining IS by representing future generations’ potential interests and concerns. We institute IS dilemma game with three forms of decision-making mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 121 publications
(219 reference statements)
0
4
0
Order By: Relevance
“…Shahrier et al [36] and Timilsina et al [37], who studied ISDG with Bangladeshi and Nepalese participants, respectively, showed that rural people tended to choose sustainable options more frequently than urban people did. On the other hand, Koirala et al [38] found that gender was not a significant factor in their ISDG in which university students participated. Timilsina et al [37] found that there were no significant differences in the choice of the sustainable option by gender, education, income, and single-family status in their ISDG of 102 Nepalese.…”
Section: Demographic Attributesmentioning
confidence: 92%
“…Shahrier et al [36] and Timilsina et al [37], who studied ISDG with Bangladeshi and Nepalese participants, respectively, showed that rural people tended to choose sustainable options more frequently than urban people did. On the other hand, Koirala et al [38] found that gender was not a significant factor in their ISDG in which university students participated. Timilsina et al [37] found that there were no significant differences in the choice of the sustainable option by gender, education, income, and single-family status in their ISDG of 102 Nepalese.…”
Section: Demographic Attributesmentioning
confidence: 92%
“…The consensus regarding its definition, measurement and magnitude is yet to be reached (Maebayashi and Konishi, 2021;D'Erasmo et al, 2016;Afonso, 2005;Blanchard et al, 1991;Buiter, 1985). Furthermore, the lack of agreement over its measurement adds to the challenges already faced by financial experts (Koirala et al, 2021;Werding, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Looking at governments' increasing reliance on borrowings, many economists have anticipated that such a situation is heading towards a "debt trap" (Rengel, 2020;Sovacool and Walter, 2019). When confronted with an environment of high deficits, the debt trap is the sustainability problem, which is perceived to be a long-term issue related to the government's budgetary position (de-C ordoba et al, 2022;Koirala et al, 2021;Gebhardt and Siemers, 2020;Schaltegger and Weder, 2014). The long-term imbalances in the government's resources or budgets give rise to unsustainable public debt (Butkus et al, 2021;Briceño and Perote, 2020;Ari and Koc, 2018;Jha and Sharma, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations